Economic Circumstances of Children Living in Higher and Lower-Educated Families and the Contribution of Household Structure: A Cross-Country Comparison with a Child’s Perspective - Heiskala, Laura; Tuominen, Minna; Erola, Jani; Kilpi-Jakonen, Elina (Tallinn University, 2026)
We study the contribution of household structure – such as the number of adults and children in the household – to the income gap between higher and lower-educated families. We extend our perspective and unit of analysis from the adults to the children living in households and study differences in children’s economic circumstances between higher and lower-educated families. More specifically, we ask: 1) To what extent are the differences in the economic circumstances of children living in higher and lower-educated households due to differences in household structure? 2) Does this vary between European countries? We study these questions using cross-nationally comparable data from the Generations and Gender Survey (GGS) and apply the Blinder-Oaxaca decomposition technique to show what the income gap would be if all education groups had the same household structure. In each country studied, children living in highly educated households have better economic circumstances. Children living in highly educated households also live more often in two-adult families, have fewer siblings living with them, and their parents are older when entering parenthood compared to others. Overall, our results show that the extent to which household structure explains income disparities varies in relative terms, but is surprisingly similar across countries in absolute terms. Despite the highly heterogeneous country sample, the results suggest that household composition contributes to a relatively limited extent overall to differences in children’s economic circumstances by parental education level. This suggests that family policies have a relatively limited impact in equalising economic disparities among children.